2020
DOI: 10.1111/opo.12719
|View full text |Cite
|
Sign up to set email alerts
|

When is refraction stable following routine cataract surgery? A systematic review and meta‐analysis

Abstract: Purpose We systematically reviewed the literature to investigate when refraction is stable following routine cataract surgery implanting monofocal intraocular lenses. Current advice recommends obtaining new spectacles 4–6 weeks following surgery. Due to advancements in surgical techniques, we hypothesised that refractive stability would be achieved earlier, which could have major short‐term improvements in quality of life for patients. Methods Medline, CINAHL, AMED, Embase, Web of Science and the Cochrane Libr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…In a subsequent analysis using 186 patients who underwent cataract surgery with Akreos Adapt AO IOL, we found a similar overall result that group D showed a reduced MAE2 (MAE based on the second examination) compared to MAE1 although it did not reach statistical significance, which might be related to small sample numbers (data not shown). Fifth, although previous literature reported that postoperative refraction stabilizes between 1 and 4 weeks following uneventful surgery, the refractive outcome measured at 1-month postoperatively may not be stable, requiring longer-term follow-up [27][28][29][30][31] .…”
Section: Discussionmentioning
confidence: 97%
“…In a subsequent analysis using 186 patients who underwent cataract surgery with Akreos Adapt AO IOL, we found a similar overall result that group D showed a reduced MAE2 (MAE based on the second examination) compared to MAE1 although it did not reach statistical significance, which might be related to small sample numbers (data not shown). Fifth, although previous literature reported that postoperative refraction stabilizes between 1 and 4 weeks following uneventful surgery, the refractive outcome measured at 1-month postoperatively may not be stable, requiring longer-term follow-up [27][28][29][30][31] .…”
Section: Discussionmentioning
confidence: 97%
“…It is difficult to find in the literature studies about visual quality of patients with corneal edema after cataract surgery. There is abundant literature concerning clinical refraction stabilization of patients without post-surgical complications [ 23 , 25 ], but the situation changes in corneal edema patients. This may be because poor visual quality in these patients is assumed, and because visual quality depends on the severity of corneal edema, introducing large variability in the samples.…”
Section: Discussionmentioning
confidence: 99%
“…The mean astigmatism remained stable over both periods, and this supports a more recent conclusion. [ 23 ] A change in astigmatism from + 0.25DCX100 to + 0.50DCX30 appears insignificant, but the difference in the axis results in an induced change in astigmatism of + 0.71DCX23. This example illustrates why the induced astigmatic powers, in Tables 1 and 2 , exceeded the difference in mean astigmatic powers revealed by refraction.…”
Section: Discussionmentioning
confidence: 99%
“…Could a change in K after phacoemulsification impact on the astigmatism revealed by refraction? The refractive error is moderately stable 1 week after uncomplicated phacoemulsification,[ 23 ] but changes in astigmatism are not unusual more than 1 month later. The normal corneal surface is elliptical[ 24 25 26 ] and the off-axis astigmatism can be estimated.…”
mentioning
confidence: 99%